1999
DOI: 10.1111/j.1469-7793.1999.0315r.x
|View full text |Cite
|
Sign up to set email alerts
|

A re‐examination of adult mouse nicotinic acetylcholine receptor channel activation kinetics

Abstract: 1. Cell-attached single-channel recordings of NMDA channels were carried out in human dentate gyrus granule cells acutely dissociated from slices prepared from hippocampi surgically removed for the treatment of temporal lobe epilepsy (TLE). The channels were activated by ¬_aspartate (250-500 nÒ) in the presence of saturating glycine (8 ìÒ). 2. The main conductance was 51 ± 3 pS. In ten of thirty granule cells, clear subconductance states were observed with a mean conductance of 42 ± 3 pS, representing 8 ± 2 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(142 citation statements)
references
References 59 publications
12
129
1
Order By: Relevance
“…The blocking and binding constants were slightly affected, consistent with other studies demonstrating that mutations at the αM4 domain do not modify significantly the binding sites or the ion pore. 22,34,40,41 The same effects on the effective opening and closing rate constants produced by αF426W were also observed in another study using choline as the agonist. 25 On the basis of our results and the aforementioned studies, we demonstrated that position αF426 is highly vulnerable to changes in side-chain identity, and that the increase in receptor functionality arises from an optimal channel transition from the closed to the open state; however, allosteric transitions within these domains are also possible and should not be excluded.…”
Section: Discussionsupporting
confidence: 60%
“…The blocking and binding constants were slightly affected, consistent with other studies demonstrating that mutations at the αM4 domain do not modify significantly the binding sites or the ion pore. 22,34,40,41 The same effects on the effective opening and closing rate constants produced by αF426W were also observed in another study using choline as the agonist. 25 On the basis of our results and the aforementioned studies, we demonstrated that position αF426 is highly vulnerable to changes in side-chain identity, and that the increase in receptor functionality arises from an optimal channel transition from the closed to the open state; however, allosteric transitions within these domains are also possible and should not be excluded.…”
Section: Discussionsupporting
confidence: 60%
“…Salamone et al, 1999;Hatton et al 2003). This is not much different from the value originally found in frog muscle (30000 s −1 at 11° C; Colquhoun & Sakmann, 1985).…”
Section: Diliganded Receptorsmentioning
confidence: 44%
“…Colquhoun & Sakmann (1985) found little evidence for a difference in frog muscle receptors. Using more recent methods, it has been suggested that there is little difference between the two sites in the adult form of the mouse receptor (Salamone et al, 1999). These authors found a significantly better fit if the sites were not assumed to be equivalent, but had similar equilibrium constants for binding.…”
Section: Monoliganded Receptorsmentioning
confidence: 72%
See 2 more Smart Citations